Pandemic influenza H1N1 outbreak in the military school - Mladenović Jovan; Čekanac Radovan; Lazić Srđan; Jadranin Željko; Dimitrije Tasić; Nedeljković Jasminka; Pavlović Miroslav (Vojnosanitetski Pregled)
Background/Aim. The first cases of the pandemic pH1N1 influenza virus infection was observed in the United States and Mexico in April 2009 and the first laboratory confirmed case in Serbia was registered in June 2009. The aim of this paper was to report on the investigation of the first confirmed outbreak of the 2009 pandemic H1N1 influenza in Serbia and to describe the clinical and epidemiologic findings from this investigation. Methods. Descriptive and analytical epidemiological methods were used. Data were collected from medical records of the Military School students and epidemiological questionnaire. Pandemic H1N1 infection was initially confirmed by the RT-PCR assay in nasopharyngeal and oropharyngeal swabs and subsequently by the complement fixation test in serum samples. Results. The attack rate of acute respiratory illness was 70.8% (204/288). Pandemic H1N1 virus infection was confirmed in 44 of 82 tested cases of acute respiratory illness (53.7%) The most common clinical manifestations of pandemic influenza H1N1 were fever (88.6%), cough (61.4%), malaise (38.6%), runny nose (36.4%), headache (29.6%), sore throat (20.5%) and muscle pain (15.9%). Conclusion. The findings from this investigation suggest that pandemic H1N1 influenza in a high military school was widespread but did not cause severe illness.